Reproduction-related variation in carbon allocation to woody tissues in Fagus crenata using a natural 13C approach. (28th November 2016) - Han, Qingmin; Kagawa, Akira; Kabeya, Daisuke; Inagaki, Yoshiyuki
Abstract : The contribution of new photo-assimilates and stored carbon (C) to plant growth remains poorly understood, especially during reproduction. In order to elucidate how mast seeding affects C allocation to both reproductive and vegetative tissues, we measured biomass increase in each tissue, branch starch concentration and stable C isotope composition (δ 13 C) in bulk leaves, current-year shoots, 3-year branches and tree rings in fruiting and non-fruiting trees for 2 years, as well as in fruits. We isolated the effect of reproduction on C allocation to vegetative growth by comparing 13 C enrichment in woody tissues in fruiting and non-fruiting specimens. Compared with 2‰ 13 C enrichment in shoots relative to leaves from non-fruiting trees, fruiting reduced the enrichment to 1‰ and this reduction disappeared in the following year with no fruiting, indicating that new photo-assimilates are preferentially used for woody tissues even with fruiting burden. In contrast, fruits had up to 2.5‰ 13 C enrichment at mid-summer, which dropped thereafter, indicating that fruit production relies on C storage early in the growing season then shifts to current photo-assimilates. At this tipping point, growth of shoots and cupules had almost finished and nuts had a second rapid growth period thereafter. Together with shorter shoots but higher biomass increment per length in fruiting trees than non-fruiting trees, these results indicate that the C limitation due to fruit burden is minimized by fine-tuning of allocation of old C stores and new photo-assimilates, along with the growth pattern in various tissues. Furthermore, fruiting had no significant effect on starch concentration in 3-year-old branches, which became fully depleted during leaf and flower flushing but were quickly replenished. These results indicate that reproduction affects C allocation to branches but not its source or storage. These reproduction-related variations in the fate of C have implications for evaluating forest ecosystem C cycles during climate change.